High-selenium exposure is associated with modulation of serum lipid metabolism - Yong Tan; Zixiong Zhang; Jinru Yang; Li Wang; Guogen Sun; Yishan Guo; Ying Xiang; Yi Zou; Xiusheng Song; Minglong Li; Chuying Huang (Ecotoxicology and Environmental Safety, 2025)
At present, there is no consensus on the relationship between selenium (Se) exposure and human serum lipid metabolism. The etiological role of high-Se exposure in lipid markers, dyslipidemia, and nonalcoholic fatty liver (NAFLD) remains unclear. We used serum untargeted metabolomics analysis to evaluate whether high-Se exposure is cross-sectionally associated with lipid metabolism in adults from high-Se exposure area (n = 112) and control area (n = 101) in Hubei Province, China. An untargeted liquid chromatography/mass spectrometry (LC/MS)-based metabolomic analysis identified 144 differential pathways and yielded 204 differentially abundant metabolites, including 32 lipid metabolites associated with lipids profiles. To further explore the correlation between Se exposure and serum lipid metabolism, we measured serum levels of lipid profiles among all the people, including serum cholesterol (CHOL), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and apolipoprotein B (APOB). The average serum Se level of the high-Se exposure group was 537.18 μg/L, significantly higher than 72.98 μg/L in the control group (p < 0.0001). The measurement levels of serum TG, LDL-C, HDL-C, and APOB in the high-Se exposure group were 1.03 (0.76, 1.34) mmol/L, 2.25 ± 0.48 mmol/L, 1.12 ± 0.24 mmol/L, and 0.77 ± 0.15 g/L, respectively, while the control group were 1.13 (0.84, 1.80) mmol/L, 2.56 ± 0.61 mmol/L, 1.02 ± 0.22 mmol/L, and 0.83 ± 0.16 g/L, respectively (all p values <0.05). Correlation analysis showed a significant negative correlation between serum Se and CHOL (r = -0.201, p < 0.01), serum Se is also associated with metabolomics markers, the negative correlation includes glyceric acid and ect., the positive correlation includes phosphorylcholine and ect. Our study suggests that high-Se exposure is negatively associated with serum lipid profiles and decreases the risk of high-TC and HDL-C dyslipidemia.